1988
DOI: 10.1080/00050068808255599
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the current and future directions of professional psychology in Acute general hospitals in australia

Abstract: Current functions and future directions of Australian hospital psychologists were assessed in a survey returned by 34 administrators of large acute general medical hospitals throughout Australia. l h e results indicated that although there appeared to he a large nuniber of roles for psychologists. their contrihution was most likely to be restricted to five treatment areas (neurology, psychosomatic medicine, death and dying, paediatrics, substance abuse). Future trends suggested an increase in three major servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The national ratio of FTE psychologists to acute public hospital beds identified in this study was 1:62—yielding a ratio of approximately 0.16 FTE psychology staff for every 10 beds. This represents a notable increase in staffing levels since the psychology workforce was last surveyed approximately twenty years ago—reporting at that time a ratio of 1:367 beds (Groth‐Marnat, ). The large variation in the size of hospitals surveyed, however, suggests that FTE to bed ratios might be more meaningfully explored as a function of hospital size (small, medium, and large).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The national ratio of FTE psychologists to acute public hospital beds identified in this study was 1:62—yielding a ratio of approximately 0.16 FTE psychology staff for every 10 beds. This represents a notable increase in staffing levels since the psychology workforce was last surveyed approximately twenty years ago—reporting at that time a ratio of 1:367 beds (Groth‐Marnat, ). The large variation in the size of hospitals surveyed, however, suggests that FTE to bed ratios might be more meaningfully explored as a function of hospital size (small, medium, and large).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant for psychology services, with data indicating that 82% of psychologists work in major cities (Health Workforce Australia, ) and therefore, unsurprisingly, the majority of hospital‐based psychology services are located in larger metropolitan hospitals. Australian data suggest that where inpatient psychological services are provided, they typically target the areas of mood, cognitive function, cancer/palliative care, diabetes, substance misuse, brain injury, eating disorders, and chronic pain (Groth‐Marnat, ; Touyz, Blaszczynski, Digiusto, & Byrne, )—the latter three also being most commonly identified in the international literature (Humbke et al., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, a substantial number reported that their training had not adequately prepared them for their professional activities. Groth-Marnat (1988) reported that the majority of large teaching hospitals in Australia employ at least one clinical psychologist, not infrequently in areas unrelated to traditional mental health or psychiatry, such as in neurology, coronary care, and pain control. In this s w e y of hospital administrators, some of the nominated growth areas for clinical psychologists were in emergency services, substance abuse, and working with the terminally ill.…”
Section: The Changing Face Of Health Psychologymentioning
confidence: 99%
“…Nevertheless, there have been some attempts to survey medical psychology in Australia (Groth-Marnat, 1988), Germany (Herzog & Hartmann, 1990), South-Africa (Schlebusch & Simpson, 1987) and the United States of America [USA] (Tovian, Rozensky, & Sweet, 2003;Pate & Kohout, 2005).…”
Section: Medical Psychology In the International Contextmentioning
confidence: 99%